In Vitro Bioavailability-Based Assessment of the Contribution of Wild Fruits and Vegetables to Household Dietary Iron Requirements Among Rural Households in a Developing Country Setting: The Case of Acholi Subregion of Uganda - Tuyizere, Jean Damascene; Okidi, Lawrence; Elolu, Samuel; Ongeng, Duncan (Food Science & Nutrition, 2021)
Wild fruits and vegetables (WFV) are believed to contain substantial quantities of micronutrients and are commonly consumed in rural areas of developing countries endowed with natural vegetation. Previous studies that provided evidence on the contribution of WFV to household micronutrient intake in a developing country setting did not consider the effect of antinutritional factors. Therefore, applying the in vitro bioavailability assessment technique and using the Acholi subregion of Uganda a case area, this study examined the contribution of commonly consumed WFV to the pooled annual household dietary requirement for iron. Laboratory analysis showed that the concentration of antinutrients varied with plant species but the pool was dominated by phytate (10.5–150 mg/100 g) and phenolic substances (38.6–41.7 mg GAE/g). In vitro iron bioavailability varied with plant species was quantitatively higher from vegetables than fruits by 27% although total concentration of the micronutrient was higher in fruits than vegetables by 142%. Nutritional computation, taking into account, household composition, and physiological status revealed that consumption of WFV resulted in a median contribution of 1.8% (a minimum of 0.02 and a maximum of 34.7%) to the pooled annual household dietary iron requirements on the basis of bioavailable iron fraction. These results demonstrate that WFV contributes meagerly to household iron needs but may serve other dietary and non-nutrient health purposes.
Keywords: antinutrients, household annual dietary iron requirements, iron bioavailability, wild fruits and vegetables